The relationship of affective and continuance organizational commitment with correctional staff occupational burnout: a partial replication and expansion study - Garland, Brett (Criminal justice and behavior, 2014)
Finding strategies to prevent burnout is imperative for correctional administrators. Ordinary least squares regression analyses of survey results from 160 employees at a private prison for offenders aged 14 to 19 who were tried as adults were used to examine the effects of affective and continuance commitments on the three dimensions of staff burnout. The results indicate that affective commitment had a negative association with emotional exhaustion, depersonalization, and feelings of reduced accomplishment, while continuance commitment had a positive relationship with these dimensions of burnout. Of the control variables, tenure had a positive association with emotional exhaustion, age had a negative relationship with depersonalization, and average daily contact with inmates had a positive association with feelings of reduced accomplishment. One strategy that administrators could employ to reduce staff burnout is to strengthen staffs? emotional ties and feelings of loyalty to the organization, while attempting to decrease perceptions that the employee is trapped in the job.